Molecular epidemiology of HIV-1 circulating among injecting drug users in the great Lisbon - Sousa, Carina (2013)
Molecular epidemiology of HIV-1 circulating among injecting drug users in the Greater Lisbon Carina Sousa1; Sandra Videira e Castro1; Elizabeth Pádua3; Ricardo Parreira1,2; Aida Esteves1,2; João Piedade1,2 1Grupo de Virologia, UEI de Microbiologia Médica; 2Unidade de Parasitologia e Microbiologia Médicas (UPMM) Instituto de Higiene e Medicina Tropical, Universidade Nova de Lisboa Rua da Junqueira nº100, 1349-008 Lisboa, Portugal 3Laboratório de Referência da Sida, Instituto Nacional de Saúde Dr. Ricardo Jorge Avenida Padre Cruz, 1649-016 Lisboa, Portugal Background and Objectives HIV/AIDS is recognized as a public health problem partly because of the high degree of viral genetic diversity that poses a major challenge for diagnosis, prevention by vaccination and treatment. Human immunodeficiency virus type 1 (HIV-1) genetic variants are classified in 4 phylogenetic groups: M, N, O and P. Group M, responsible for the great majority of HIV-1 infections worldwide, can be further subdivided into 9 phylogenetic subtypes (A–D, F–H, J and K) and, at least, 6 sub-subtypes (A1–A4 and F1–F2). Genetic recombination events, during infection with multiple subtypes, continuously give rise to mosaic viruses (unique recombinant forms, URFs), some of which can gain epidemic proportions (circulating recombinant forms, CRFs). According to their cellular coreceptor (CCR5 or CXCR4), HIV-1 variants can be also classified as R5-tropic, X4-tropic or dual/mixed (R5X4). Besides recombination, the main causes that contribute to HIV-1 impressive genetic heterogeneity are the lack of proof-reading ability by reverse transcriptase, the rapid viral turnover in vivo and host selective immune and drug pressures. These mechanisms, taken together, lead to the rapid formation, at the individual level, of distinct viral micropopulations, genetically related to each other, known globally as quasispecies, providing evidence for the ongoing evolution of HIV-1. In order to achieve an update picture of the molecular epidemiology of HIV-1 strains circulating among intravenous drug users (IDUs) from the Greater Lisbon, the aims of this study were: • to assess the genetic diversity of pol protease (PR), reverse transcriptase (RT), integrase (IN) and env C2V3C3 coding sequences; • to estimate the frequency of coreceptor usage (CCR5 and/or CXCR4). Results and Discussion RNA extracted from plasma taken from 61 HIV-1 seropositive IDUs, collected between 1998 and 2009, was amplified by nested PCR, after in vitro reverse transcription, to originate PR, RT, IN and C2V3C3 amplicons of 460, 650, 906 and 565 bp, respectively. A total of 158 DNA sequences was obtained, from 49 samples successfully amplified for, at least, one of the regions, by sequencing of PCR products or plasmid clones. Following sequence editing using BioEdit v.7.0.9.0 (Hall, 1999), subtype characterization was performed by manual phylogenetic analysis with MEGA4 (Tamura et al., 2007) and recombinant analysis was carried out by bootscanning using SimPlot v.3.5.1 (Lole et al., 1999). This study revealed a significant degree of HIV-1 diversity, suggesting the existence of a heterogeneous epidemic among the IDUs studied. On the whole, HIV-1 non-B subtypes were identified in 58.9% (93/158) of the sequences obtained: PR in this population comprehend mainly subtypes B and G, with a clear indication of the presence of a significant proportion of recombinants, mostly comprising unique mosaic structures of these two subtypes, CRF02_AG and CRF14_BG. Finally, 35 putative amino acid V3 sequences were obtained and coreceptor usage prediction (genotypic) was accomplished using the 11/25 (Fouchier et al., 1992) and the V3 net charge empiric rules (De Jong et al., 1992) and also the programs Fortinbras PSSM [matrix: subtype B X4/R5 (Poveda2009)] (at http://fortinbras.us/cgi-bin/fssm/fssm.pl) and geno2pheno[coreceptor] v.1.2. (at http://coreceptor.bioinf.mpi-inf.mpg.de/index.php), with a significance level of 20%. Considering the discrepant results obtained for some of the sequences, we considered as X4/R5X4-tropic all the sequences with coincident previsions with at least two of the algorithms used. Therefore, 30 sequences were identified as R5-tropic and five as X4 or dual/mixed-tropic. Overall, the prediction discrepancies were more frequent in non-B subtypes and in sequences with shorter V3 loops (34 amino acids), which may reflect a lower suitability of the matrices used in these cases 12 B, 1 F1, 17 G/G(14_BG), 5 CRF02_AG, 6 URFs; n=41; RT 17 B, 1 F1, 13 G/G(14_BG), 5 G(02_AG), 5 URFs; n=41; IN 13 B, 1 F1, 12 G/G(14_BG), 1 CRF02_AG, 14 URFs; n=41; and C2V3C3 [8 A, 23 B, 1 F1, 3 G; n=35]. It is also significant that 45.2% (19/42) of the PR/RT/IN/C2V3C3 concatenated sequences were derived from inter-genotype recombinants. Overall, the viral forms circulating Conclusions This study represents a contribution to a more complete understanding of the molecular epidemiology of the HIV/AIDS epidemic in IDUs of the Greater Lisbon. Our data confirm that this HIV-1 epidemic is dominated by B and G subtypes, and their recombinant forms. However, other subtypes (A, F1) and recombinant forms (CRF02_AG) were also found. This finding confirms our previous data and suggests that the HIV-1 epidemic in Portugal may be evolving to a unique epidemiological pattern, in which subtypes B, G and their recombinant forms prevail. The high prevalence of patients infected with R5-tropic viruses makes a CCR5 antagonist-based therapeutic regimen an option to be considered in this population, if necessary. However, the genotypic methods for coreceptor prediction still present limitations, especially when analysing non-B or genetically divergentstrains. Anyway, these methods are viable alternatives whenever phenotypic testing is not possible and they should be optimized in order to improve the sensibility and specificity of their predictions References Hall, Thomas. BioEdit: a user-friendly biological sequence alignment editor and analysis program for Windows 95/98/NT. Nucleic Acids Symposium Series, v.41, p.95-98. (1999). Tamura, Koichiro, et al. MEGA4: Molecular evolutionary genetics analysis (MEGA) software version 4.0. Molecular Biology and Evolution, v.24, p.1596-1599. (2007). Lole, Kavita, et al. Full-length human immunodeficiency virus type 1 genomes from subtype Cinfected seroconverters in India, with evidence of intersubtype recombination. Journal of Virology, v.73, p.152-160. (1999). Fouchier, Ron, et al. Phenotype-Associated Sequence Variation in the Third Variable Domain of the Human Immunodeficiency Virus Type 1 gpl20 Molecule. Journal of Virology, v.66, p.3183-3187. (1992). De Jong, Jean-Jacques, et al. Minimal Requirements for the Human Immunodeficiency Virus Type 1 V3 Domain To Support the Syncytium-Inducing Phenotype: Analysis by Single Amino Acid Substitution. Journal of Virology, v.66, p. 6777-6780. (1992).